The Impact of the COVID-19 Pandemic on Premenstrual Symptoms and Its Relationship with the Quality of Life - Bulut, Aleyna; Aydın Kartal, Yasemin (Nursing and Health Sciences Journal (NHSJ), 2023)
Lifestyle changes can negatively affect premenstrual symptoms. The purpose of this study is to determine the effect of changes in the lifestyle of students on premenstrual symptoms and their relationship with their quality of life during the global epidemic process. The research that was planned with a descriptive and correlational pattern was conducted who receive education in the Faculty of Health Sciences in the structure of a public university in İstanbul. The sample of the study consisted of 336 female students. “The Personal Information Form”, “the Scale of Premenstrual Syndrome (PMSS)”, “the Scale of Life Quality Short Form - SF-36” was implemented upon the students that were included in the study. The total PMSS score of the students participating in the study was 147.12±37.41. It was determined that 32.4% of the students had Covid-19 infection. When the total mean scores of PMSS were evaluated according to the lifestyle behaviors of the students; It was determined that PMSS total score differed significantly according to appetite status, exercise, tea and coffee consumption and sleep patterns. According to the results of the study, it was determined that nutritional behaviors, physical activity status, sleep and stress levels changed greatly with the COVID-19 epidemic and it affected PMS. It was determined that this situation affected the quality of life negatively both physically and mentally.